2011
DOI: 10.1590/s1806-37132011000100004
|View full text |Cite
|
Sign up to set email alerts
|

Ansiedade e depressão em pacientes com asma: impacto no controle da asma

Abstract: Objective: There is evidence that asthma is associated with an increase in psychiatric symptoms and mental disorders. This association can make it difficult to achieve asthma control. The purpose of this study was to determine whether the level of asthma control is associated with anxiety and depression. Methods: A crosssectional study involving 78 patients with confirmed moderate or severe asthma and under regular treatment at the Asthma Outpatient Clinic of the Federal University of São Paulo Hospital São Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 27 publications
2
20
1
3
Order By: Relevance
“…Recent studies in adults show that effective control of asthma is associated with fewer mental health problems in clinical settings (Kardos et al . 2011; Vieira et al . 2011), compared to uncontrolled asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in adults show that effective control of asthma is associated with fewer mental health problems in clinical settings (Kardos et al . 2011; Vieira et al . 2011), compared to uncontrolled asthma.…”
Section: Discussionmentioning
confidence: 99%
“…One additional and still not broadly recognized aspect of asthma is its association with affective disorders such as anxiety . Indeed, research showed that around 80% of asthmatic patients have uncontrolled anxiety . Importantly, several animal studies modeling asthma confirmed association of asthma symptoms to higher levels of anxiety .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, research showed that around 80% of asthmatic patients have uncontrolled anxiety . Importantly, several animal studies modeling asthma confirmed association of asthma symptoms to higher levels of anxiety . While mechanistic understanding of this link is under investigation, it is becoming evident that managing anxiety is important for the asthma patient treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic of the reversible inflammatory process in asthma and a good response to therapeutic measures characterize the evolution of the disease, which is marked by intermittent exacerbations (70)-(72). However, the lack of these symptoms can define a subgroup of patients who are considered hypoperceivers and who evolve with a worse prognosis for disease control (73).…”
Section: Introductionmentioning
confidence: 99%